Influence of Supervisory Relationship and Satisfaction among Trainee Counselors in Practicum Process - Ghazali, N.M.; Taha, M.; Wan Jaafar, W.M.; Anuar, Ayob; Yahya, F.; Roose, M.A.R. (UNIMAS Publisher, 2016)
The purpose of this research is to investigate the influence of supervisory relationship on supervision satisfaction among trainee counselors. The Supervisory Relationship Questionnaire (SRQ) is to measure the supervisory relationship and Supervisory Sat-isfaction Questionnaire (SSQ) is used to measure supervision satisfaction. The find-ing shows that supervisory relationship and its subscales (Safe Base, Structure, Commitment, Reflective Education, Role Model and Formative Feedback) have a positively significant relationship with supervision satisfaction among trainee coun-selors (safe base: r = 0.73, p < 0.05, structure: r = 0.65, p < 0.05, commitment: r = 0.69, p < .05, reflective education: r = 0.70, p < 0.05, role model: r = 0.51, p < 0.05, formative feedback: r = 0.71, p < 0.05 and supervisory relationship: r = 0.79, p < 0.05). The findings of this research also found that supervisory relationship, safe base and role model variables have significant influence on supervision satisfaction among trainee counselors with F (1, 98) = 169.59, p < 0.05, Adjusted R2 = 0.63 for supervi-sory relationship variable, F (3, 96) = 68.68, p < 0.05, Adjusted R2 = 67 for safe base variable and F (2, 97) = 96.47, p < 0.05, Adjusted R2 = 0.65 for role model variable. Supervisory relationship variable has the greatest influence (β = .79) while role mod-el variable has the least influence (β = - 0.28) on supervision satisfaction. As for the theoretical implication, the finding of this research has proven Marina Palomo’s theo-retical framework in ‘Bi-directional Model of the Supervisory Relationship’. Mean-while in practical implication, this research has raised awareness on the importance of supervisory relationship on supervision satisfaction in counseling supervision.